The Role of Teachers in Learning Patterns of Aqidah Akhlak Material for Children with Special Needs at the Inclusive Madrasah MI Ar-Roihan Malang Academic Year 2022-2023 - Nurul Salis Alamin; Syarifah; Saiful Anwar; Jaziela Huwaida; Alfi Nur Rosyidah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This research aims to 1) explain the learning patterns of moral beliefs for children with special needs in inclusive madrasas 2) discuss the application of learning patterns of moral beliefs for children with special needs in inclusive madrasas 3) the role of teachers in implementing the learning patterns of moral beliefs for children with special needs in inclusive madrasas . In this research, a case study-based qualitative method was used. Researchers used interviews, observations and documentation to answer three research objectives. Research results 1) learning patterns for moral belief material, namely teachers and children, teachers and children and tools, teachers and children and media. 2) implementation of the learning pattern of moral beliefs applied in activities around the school with Duha prayers, reading the Asmaul Husna and guidance and advice on good habits and implemented in intracurricular, extracurricular and curricular areas. 3) the role of the teacher in learning moral beliefs with the teacher's role as facilitator, guide, motivator and inspirer. And researchers found new findings regarding the role of teachers as visual support in the implementation of learning moral beliefs. This research found that there has been a pattern of learning moral beliefs for children with special needs on the grounds that there is a teacher's role so that the implementation of learning moral beliefs for children with special needs is implemented. It is hoped that other inclusive schools will implement and improve learning patterns of moral beliefs by implementing learning as well as the mentoring role of guidance and counseling teachers, so that inclusive schools can study and implement learning patterns that are appropriate to students.